Building information modeling for airports - McCuen, Tamera L. 1964-; Pittenger, Dominique M. 1975- (Transportation Research Board, 2016)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 70: Building Information Modeling for Airports summarizes current state of the art and practice for Building Information Modeling (BIM). BIM is a digital representation of a facility's physical and functional characteristics. BIM offers tools that allow airport decision makers to understand all components of a facility--their location, and their attributes, both graphically and systematically--to minimize the total cost of owning and operating an airport facility. The report provides a snapshot of experiences related to the emergence of BIM in North American airports.
At head of title: Airport Cooperative Research Program.
"A Synthesis of Airport Practice."
Keywords: Building information modeling -- North America.; Airports -- North America -- Management.; Airports -- North America -- Management -- Data processing.; elektronické knihy; electronic books